2012
DOI: 10.1002/cpe.2831
|View full text |Cite
|
Sign up to set email alerts
|

A high‐productivity task‐based programming model for clusters

Abstract: Programming for large-scale, multicore-based architectures requires adequate tools that offer ease of\ud programming and do not hinder application performance. StarSs is a family of parallel programming models\ud based on automatic function-level parallelism that targets productivity. StarSs deploys a data-flow model: it\ud analyzes dependencies between tasks and manages their execution, exploiting their concurrency as much\ud as possible.\ud This paper introduces Cluster Superscalar (ClusterSs), a new StarSs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 20 publications
0
28
0
1
Order By: Relevance
“…In the literature, different approaches have been proposed. ClusterSs [13] has a master-slave model where a master process is responsible for maintaining this global view and delegates actual numerical work to other processes. The authors showed that the extreme centralization of this model prevented it from achieving high performance at scale.…”
Section: Algorithm 2 Trsm Kernel Of the Ptg Tile Choleskymentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, different approaches have been proposed. ClusterSs [13] has a master-slave model where a master process is responsible for maintaining this global view and delegates actual numerical work to other processes. The authors showed that the extreme centralization of this model prevented it from achieving high performance at scale.…”
Section: Algorithm 2 Trsm Kernel Of the Ptg Tile Choleskymentioning
confidence: 99%
“…StarSs is a suite of runtime systems developed at the Barcelona Supercomputing Center and supporting the STF model. Among them, ClusterSs [13] provides an STF support for parallel distributed memory machines with a master-slave interaction scheme. OmpSs [14] targets SMP, SMP-NUMA, GPU and cluster platforms.…”
Section: Short Review Of Task-based Runtime Systems For Distributed Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of SDF, several frameworks such as KAAPI [19] or StarSS [32,36] exist, which ease the programming of multi-threaded implementations. Both provide libraries for the concurrent execution of nodes and the communication, which are based on a task model.…”
Section: Related Workmentioning
confidence: 99%
“…An extended description of the ClusterSs design, programming model, implementation and productivity study can be found in [7].…”
Section: Introductionmentioning
confidence: 99%